2001
DOI: 10.1046/j.1365-2052.2001.00744.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and mapping of microsatellites from a microdissected BTA 11‐specific DNA library

Abstract: A chromosome-specific library was developed for Bos taurus autosome 11 by chromosome microdissection and microcloning using a bovine primary fibroblast culture, obtained from a t(X;23) heifer, that spontaneously developed a translocation chromosome involving bovine chromosome 11. The library was screened using (AC)12 oligos, positive clones selected, sequenced and primers developed to generate bovine chromosome 11-specific microsatellite markers. This study suggests that chromosome-specific libraries have grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…It is known that a duplication of the IgM locus exists on BTA11 (16). PCR was carried out with primers Cm forward and Cm reverse ( Table 1) using DNA from a lambda library prepared speci®cally from bovine chromosome 11 (17). This reaction was also carried out with BAC 944D11, a clone found to carry the J H locus isolated in our studies (see Results), and BAC 66R4C11, a clone carrying a second J H locus (18,19).…”
Section: Chromosomal Localization Of a J H Locusmentioning
confidence: 99%
“…It is known that a duplication of the IgM locus exists on BTA11 (16). PCR was carried out with primers Cm forward and Cm reverse ( Table 1) using DNA from a lambda library prepared speci®cally from bovine chromosome 11 (17). This reaction was also carried out with BAC 944D11, a clone found to carry the J H locus isolated in our studies (see Results), and BAC 66R4C11, a clone carrying a second J H locus (18,19).…”
Section: Chromosomal Localization Of a J H Locusmentioning
confidence: 99%
“…The bovine chromosome 29 library was constructed by microdissection of a 1:29 Rb-fusion cell line as described in Ambady et al (1997Ambady et al ( , 2001). The Ï-ZAP library was plated at F5,000 pfu per 150-mm LB plate and grown overnight at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Zhao et al (1999) recently reported 22 new markers from a microdissected library of porcine chr 6 (SSC6) and Wang et al (2000) isolated 31 markers from an SSC8 library. Recently, Ambady et al (2001) isolated 17 new ms markers from a BTA11-specific library and Liu et al (in press) obtained 34 new ms markers from a BTAY library. Here we report on the isolation and mapping of new markers from a bovine chromosome 29 (BTA29) library prepared by microdissection.…”
mentioning
confidence: 99%